Abnormal cardiovascular sympathetic and parasympathetic responses to physical and emotional stimuli in depersonalization disorder - Owens, Andrew P.; David, Anthony S.; Low, David A.; Mathias, Christopher J.; Sierra-Siegert, Mauricio (Frontiers in Neuroscience, 2015)
Depersonalization disorder (DPD) is characterized by subjective unreality, disembodiment, emotional numbing and reduced psychogenic sympathoexcitation. 3 related experiments used physical and emotional challenges in 14 DPD participants and 16 controls to elucidate whether the cardiovascular sympathetic (SNS) and parasympathetic (PNS) nervous systems are implicated in DPD and if blunted DPD sympathoexcitation is peripherally or centrally mediated. Participants completed the Beck Anxiety Inventory (BAI), Dissociative Experience Scale (DES) and Cambridge Depersonalization Scale (CDS). Study I recorded heart rate (HR) and blood pressure (BP) during 5mins supine baseline, 3mins handgrip (HG), 3mins cold pressor (CP) and 5mins 60°head-up tilt (HUT). Study II recorded HR, BP and heart rate variability (HRV) during 5mins HUT and unpleasant images. Study III examined HR and BP orienting responses (ORs) to HUT and unpleasant, neutral and pleasant images. DPD BAI (p=0.0004), DES (p=.0002) and CDS (p=< 0.0001) scores were higher than controls. The DPD group produced diminished diastolic BP (DBP) (p=0.045) increases to HG. Other indices were comparable between groups. DPD participants produced diminished systolic BP (SBP) (p=0.003) and DBP (p=0.002) increases, but greater (p=0.004) HR increases to CP. In study II, DPD high frequency HRV (HF-HRV) – indicating parasympathetic vagal activity - was reduced (p=0.029). In study III, DPD DBP was higher throughout the 5s duration of HUT/pseudorandom unpleasant image presentation (1s [p=0.002], 2s [p=0.033], 3s [p=0.001], 4s [p=0.009], 5s [p=0.029]). Study I’s BP pressor data supports previous findings of suppressed sympathoexcitatioin DPD. The greater HR increases to CP, decreased HF-HRV in study II, and increased DBP during unpleasant ORs in study III implicates the SNS and PNS in DPD pathophysiology. These studies suggest the cardiovascular autonomic dysregulation in DPD is likely to be centrally-mediated